Maltoma of Thyroid: A Rare Thyroid Tumour - Navisha Latheef; Vijendra Shenoy; M. Panduranga Kamath; Mahesh Chandra Hegde; A. Raghavendra Rao (Case Reports in Otolaryngology)
Introduction. Primary thyroid lymphomas constitute up to 5% of all thyroid malignancies and can be divided into non-Hodgkin’s lymphomas (NHLs) of B- and T-cell types, as well as Hodgkin’s lymphomas. Mucosa-associated lymphoid tissue (MALT) lymphomas are a relatively recently recognized subset of B-cell NHLs, and they are listed as extranodal marginal zone lymphomas according to the revised European-American lymphoma classification. Case Report. We report an uncommon case of a 44-year-old man, who noted a painless, growing mass on right side of his neck of the three-month duration. Thyroid profile was within normal limits. FNAC showed lymphocytic thyroiditis. The patient underwent a right hemithyroidectomy. The histologic examination and the immunohistochemistry showed an extra nodal marginal B-cell type maltoma (malt lymphoma). CHOP chemotherapy with rituximab was given. The clinical course has been favourable in the first year of followup, with no evidence of local or systemic recurrence of the disease. Discussion. Marginal zone lymphoma encompasses a heterogeneous group of B-cell tumours that variously arise within the lymph nodes, spleen, or extranodal tissues. A case of maltoma of thyroid is presented for its rarity and diagnostic dilemmas. Conclusion. Maltomas are slow-growing lymphomas. The optimal treatment and followup of patients with thyroid maltomas remain controversial at present.